IMPLEMENTATION OF TAX PLANNING AS AN EFFORT TO SAVING INCOME TAX FOR CORPORATE TAXPAYERS (CASE STUDY: PT JAYA PRIMA EKSPRESS) - Cut Wika Utary (KOLABORASI: Journal of Multidisciplinary, 2026)
This study aims to understand the application of tax planning at PT Jaya Prima Ekspress for income tax savings and to identify the types of tax planning implemented. Using a qualitative descriptive approach, this study uses primary data obtained directly from PT Jaya Prima Ekspress, focusing on financial statements, particularly the income statement, and other related accounting records. This method allows for in-depth exploration and systematic interpretation of the company's tax planning practices. The findings reveal that PT Jaya Prima Ekspress successfully reduced its income tax liability by Rp351,379,181 in 2024 through tax planning, reducing the tax payable from Rp7,003,679,037 to Rp6,652,299,856. This demonstrates the effectiveness of tax planning in optimizing tax liabilities and improving the company's financial efficiency within the legal framework. This study emphasizes that effective tax planning not only ensures tax compliance but also serves as a strategic tool for managing financial resources, strengthening competitiveness, and supporting long-term business sustainability.